Highly diastereoselective total synthesis of (+/-)-heritonin and (+/-)-heritol - Chavan, Subhash P.; Garai, Sumanta; Kalkote, Uttam R. (Tetrahedron, 2012)
A highly diastereoselective synthesis of heritol and heritonin by intramolecular cyclization on a preformed sensitive butenolide functionality is described. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Butenolide; cyclization; Dihydroxylation; Friedel-Crafts acylation; Tetralone

Protecting group free and scalable approach towards total synthesis of (-)-venlafaxine - Chavan, Subhash P.; Pawar, Kailash P.; Garai, Sumanta (RSC Advances, 2014)
A protecting group free asymmetric total synthesis of (-)-venlafaxine is reported. The strategy employs Sharpless epoxidation and regio-selective epoxide ring opening by an in situ generated Gilman reagent as key steps. This paper reports a 53% overall yield in 6 steps for total synthesis of (-)-venlafaxine.